THE IMPACT OF ESG PERFORMANCE TO FIRM PERFORMANCE AND MARKET VALUE - David Junius; Adriel Adisurjo; Y. Arief Rijanto; Yang Elvi Adelina (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This research aims to investigate the impact of ESG performance on firm performance and market value. Total samples used are 271 listed companies (1355 firm-years observations) in five years period (2013-2017), which consisted of four ASEAN countries (Indonesia, Malaysia, Singapore, and Thailand). This study is analyzed using multiple regression analyses with the random-effect model and descriptive statistic. The independent variable is ESG Score; the dependent variables are three performance indicators (Return on Assets, Return on Equity, and Tobin’s Q) and Price-Earnings ratio; the control variables are firm size, firm's age, financial leverage, and industry. This research contributes to broadening the scope of the literature review regardings ESG performance by analyzing it on developing countries and also by using rarely used dependent variables, market value. The finding in this research is there is no significant influence from ESG Score to Firm Performance and Market Value because ESG Score is not yet a part of firm performance measurement. This research is limited in conducting lag effect research with the lag period of only one year, and also the number of companies that already have ESG scores is limited.